The Impact of Slice Interval and Equation on the Accuracy of Magnetic Resonance Image Estimation of Quadriceps Muscle Volume in End Stage Liver Disease - Quinlan, Jonathan I.; Jones, Clare; Bissonnette, Emma; Dhaliwal, Amritpal; Williams, Felicity; Choudhary, Surabhi; Breen, Leigh; Lavery, Gareth G.; Armstrong, Matthew J.; Elsharkawy, Ahmed M.; Lord, Janet M.; Greig, Carolyn A. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: End stage liver disease (ESLD) is associated with loss of muscle mass and function, known as sarcopenia, which can increase the risk of complications of ESLD, hospitalisation and mortality. Therefore, the accurate assessment of muscle mass is essential to evaluate sarcopenia in ESLD. However, manual segmentation of muscle volume (MV) can be laborious on cross-sectional imaging, due to the number of slices that require analysis. This study aimed to investigate the impact of reducing the number of slices required for MV estimation. Further, we aimed to compare two equations utilised in estimating MV (cylindrical and truncated cone). Methods: 38 ESLD patients (23 males; 54.8±10.7 years) were recruited from the Queen Elizabeth University Hospital Birmingham. A 3T MRI scan was completed of the lower limbs. Quadriceps MV was estimated utilising 1-, 2-, 3- and 4cm slice intervals with both cylindrical and truncated cone equations. Absolute and relative error (compared to 1cm slice interval) was generated for 2-,3- and 4cm slice intervals. Results: Relative error increased with slice interval using the cylindrical (0.45% vs 1.06% vs 1.72%) and truncated cone equation (0.27% vs 0.58% vs 0.74%) for 2, 3, and 4cm respectively. Significantly, the cylindrical equation produced approximately twice the error compared to truncated cone, with 3cm (0.58% vs 1.06%, P<0.01) and 4cm intervals (0.74% vs 1.72%, P<0.001). Conclusion: The use of the truncated equation with a 4cm slice interval on MRI offers an efficient but accurate estimation of quadricep muscle volume in ESLD patients.